Stabilisation behaviour of cyclically loaded shallow foundations for offshore wind turbines - Sturm, Hendrik (KIT Scientific Publishing, 2009)
This work presents the results of model tests and numerical simulations of shallow foundations subjected to cyclic loads typical of offshore loadings. Main focus is spent on the accumulated rotational and settlement behaviour relevant in particular for fixed installed offshore wind turbines.